2019
DOI: 10.1029/2018gc007923
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Moist to Wet Source Transition Throughout the Oman‐UAE Ophiolite, and Implications for the Geodynamic History

Abstract: The Oman-United Arab Emirates (UAE) ophiolite represents the largest and best-preserved fragment of obducted oceanic lithosphere in the world. However, debate continues regarding its geodynamic history. This debate is in part a consequence of the lateral variability in the later stage magmatic units, with arc signatures considered to be well developed in the north of the ophiolite but less so in the south. In this study, we investigate later stage intrusions in the central and southern part of the ophiolite. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 108 publications
(277 reference statements)
0
8
0
Order By: Relevance
“…The tectonic setting (subduction-related basins vs. more open ocean ridge segments) during the igneous accretion of the Oman ophiolite is a long-standing debate (e.g. Coleman, 1981;Pallister and Hopson, 1981;Hopson et al, 1981;Pearce et al, 1981;Searle et al, 2004;Gray et al, 2005;Ishikawa et al, 2005;Boudier and Nicolas, 2007;Warren et al, 2007, MacLeod et al, 2013De Graaf et al, 2019;Agard et al, 2020). Plate tectonic reconstructions, imprecise during the Cretaceous normal magnetic superchron, are of little help to solve this specific problem (Granot et al, 2012).…”
Section: It Is Particularly Well Preserved Because It Is Not Yet Affected By Continental Collision Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…The tectonic setting (subduction-related basins vs. more open ocean ridge segments) during the igneous accretion of the Oman ophiolite is a long-standing debate (e.g. Coleman, 1981;Pallister and Hopson, 1981;Hopson et al, 1981;Pearce et al, 1981;Searle et al, 2004;Gray et al, 2005;Ishikawa et al, 2005;Boudier and Nicolas, 2007;Warren et al, 2007, MacLeod et al, 2013De Graaf et al, 2019;Agard et al, 2020). Plate tectonic reconstructions, imprecise during the Cretaceous normal magnetic superchron, are of little help to solve this specific problem (Granot et al, 2012).…”
Section: It Is Particularly Well Preserved Because It Is Not Yet Affected By Continental Collision Betweenmentioning
confidence: 99%
“…"P1 vs. P2") for the emplacement and crystallization of the two plutonic series is difficult to determine at the global scale, authors working on different outcrops and different lithologies reaching contrasted conclusions (e.g. Benoit et al, 1999;Python and Ceuleneer, 2003;Haase et al, 2016;Goodenough et al, 2014;Rospabé et al, 2017;De Graaf et al, 2019).…”
Section: It Is Particularly Well Preserved Because It Is Not Yet Affected By Continental Collision Betweenmentioning
confidence: 99%
“…Zircon dating has revealed that the paleocrust formed ~95 Ma ago under fast-spreading conditions with a half-spreading rate of 50 -100 mm/yr (Rioux et al, 2012). In contrast with the contemporary fast-spreading mid-ocean ridges such as the EPR, field relations and geochemical results suggest a polygenetic origin for the Oman ophiolite (e.g., de Graaff et al, 2019). The first magmatic phase produced the socalled V1 lavas and related gabbros that are very similar to the modern EPR, except that the parental MORB melts show enhanced water contents due to the influence of the regional subduction initiation (e.g., MacLeod et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of geochemical and geochronological evidence indicates that the crustal sequences of many Tethyan ophiolites -including the Oman-U.A.E. (Semail) example -formed in response to upper-plate extension during the initiation of lower-plate subduction and roll back Dilek et al, 2007;Dilek and Furnes, 2009;Guilmette et al, 2018;Ishikawa et al, 2002;MacLeod et al, 2013;Metcalf and Shervais, 2008;Rollinson, 2009;Rollinson and Adetunji, 2015;Shafaii Moghadam et al, T. M. Belgrano et al: A revised map of volcanic units in the Oman ophiolite 2013; Stern and Bloomer, 1992). These findings have led to reinterpretation of many ophiolites as counterparts to difficult-to-access magmatic records of subduction initiation preserved in submarine forearcs and arc basement ("protoarcs"; Stern et al, 2012;Stern and Bloomer, 1992;Whattam and Stern, 2011).…”
Section: Introductionmentioning
confidence: 99%